Design of a Web-Based Pain Module for a Medication Record Application to Support Pharmacist Self-Medication Services: Design of a Web-Based Pain Module for a Medication Record Application to Support Pharmacist Self-Medication Services - Dimas Adhi Pradana; Sri Haryanti; Suraya Baharun (Media Farmasi Indonesia, 2025)
Today's pharmacists' roles in healthcare services are changing quickly, and the key to staying up to date is internet-based drug records. Pharmacists have a significant impact on the field of health technology, particularly when it comes to patient medication records through the use of certain technologies. As professionals, pharmacists must play a bigger part in using digital technology to help improve patient safety and public health (patient safety). Medication records are one of the documents from pharmaceutical services carried out by pharmacists in pharmacies. Web-based pharmacist medication records can be used to document the provision of over-the-counter medications, referred to as self-medication services. This study aims to determine the usability of the web-based pharmacist medication record application developed as a supporting tool for community pharmacists in self-medication services. The research method used is Research and Development (R&D). The initial stage of the research involved interviews with 10 pharmacists to identify the needs of the application. Based on the interview results, self-medication for pain is the most common case occurring in pharmacies, so the researchers added a pain module to this application. Usability testing was conducted using the USE questionnaire to 135 respondents (45 pharmacists and 90 patients) in the city of Semarang. The test results show that the application meets usability criteria with the categories of usefulness, easy of use, easy learning, and satisfaction.